Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1523/jneurosci.1694-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Peripheral Circadian Timekeeping in a Mouse Model of Huntington's Disease and Its Restoration by Temporally Scheduled Feeding

Abstract: Behavioral circadian rhythms disintegrate progressively in the R6/2 mouse model of Huntington's disease (HD), recapitulating the sleep-wake disturbance seen in HD patients. Here we show that disturbances in circadian pacemaking are not restricted to the brain, but also encompass peripheral metabolic pathways in R6/2 mice. Notably, circadian rhythms of clock-driven genes that are key metabolic outputs in the liver are abolished in vivo. This deficiency is accompanied by arrhythmic expression of the clock genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
113
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 27 publications
(40 reference statements)
5
113
1
Order By: Relevance
“…In the HD-N171-82Q mouse model, CR improves motor performance and survival while reducing cell death (Duan et al, 2003). Prior work in the R6/2 HD model has shown that TRF can restore HD-driven disruption in circadian gene expression in the liver (Maywood et al, 2010) and improve locomotor activity as well as exploratory behavior in the open field without increasing life span (Skillings et al, 2014). Together, these data suggest that feeding schedules could play a role in the treatment of HD and could lead to the development of new treatment options for neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the HD-N171-82Q mouse model, CR improves motor performance and survival while reducing cell death (Duan et al, 2003). Prior work in the R6/2 HD model has shown that TRF can restore HD-driven disruption in circadian gene expression in the liver (Maywood et al, 2010) and improve locomotor activity as well as exploratory behavior in the open field without increasing life span (Skillings et al, 2014). Together, these data suggest that feeding schedules could play a role in the treatment of HD and could lead to the development of new treatment options for neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the R6/2 mouse model of HD the rhythmic transcription of core clock genes in the SCN and other brain regions is disrupted in vivo, but then rescued when assessed in in vitro explants, suggesting that circadian deficits are due to alterations of the intrinsic circuitry of the SCN (20,90). This is supported by a reduced circadian rhythm in spontaneous electrical activity in SCN neurons in BACHD transgenic mice (89).…”
Section: Circadian Rhythm Disruption In Hdmentioning
confidence: 99%
“…Support for this notion comes from transgenic animal models of HD, such as in the R6/2, R6/1 and BACHD mice, which have shown that circadian disruption precedes the presentation of disease features (20,89,90). Furthermore, humans with manifest HD also display circadian rhythm abnormalities, with disturbances in rest-activity profiles and abnormal day-night ratios, as well as alterations in sleep-wake timing and melatonin and cortisol profiles (20,88,91).…”
Section: Circadian Rhythm Disruption In Hdmentioning
confidence: 99%
“…Normally, SCN-regulated physiological rhythms lead to entrainment of peripheral oscillators, coordinating the cells within a tissue and resulting in rhythmic gene expression throughout the body (50,53). Even when the SCN is dysfunctional, manipulations, including glucocorticoid treatment, temporally restricted food intake, and forced exercise can entrain rhythmic gene expression rhythms in peripheral tissues (4,39,45,47,50).…”
mentioning
confidence: 99%